Validation of corporate probability of default models considering alternative use cases - Michael Jacobs (International Journal of Financial Studies, 2021)
In this study, we consider the construction of through-the-cycle ("TTC") PD models designed for credit underwriting uses and point-in-time ("PIT") PD models suitable for early warning uses, considering which validation elements should be emphasized in each case. We build PD models using a long history of large corporate firms sourced from Moody's, with a large number of financial, equity market and macroeconomic variables as candidate explanatory variables. We construct a Merton model-style distance-to-default ("DTD") measure and build hybrid structural reduced-form models to compare with the financial ratio and macroeconomic variable-only models. In the hybrid models, the financial and macroeconomic explanatory variables still enter significantly and improve the predictive accuracy of the TTC models, which generally lag behind the PIT models in that performance measure. We conclude that care must be taken to judiciously choose the manner in which we validate TTC vs. PIT models, as criteria may be rather different and be apart from standards such as discriminatory power. This study contributes to the literature by providing expert guidance to credit risk modeling, model validation and supervisory practitioners in controlling the model risk associated with such modeling efforts.
Keywords: G21; G28; M40; E47; 330; credit risk; credit underwriting; early warning systems; model risk; model validation; point-in-time; probability of default; regulatory capital; through-the-cycle